2(t-2)=6

Simple and best practice solution for 2(t-2)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(t-2)=6 equation:


Simplifying
2(t + -2) = 6

Reorder the terms:
2(-2 + t) = 6
(-2 * 2 + t * 2) = 6
(-4 + 2t) = 6

Solving
-4 + 2t = 6

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 2t = 6 + 4

Combine like terms: -4 + 4 = 0
0 + 2t = 6 + 4
2t = 6 + 4

Combine like terms: 6 + 4 = 10
2t = 10

Divide each side by '2'.
t = 5

Simplifying
t = 5

See similar equations:

| 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 | | 7x+6=3x+2 | | 2x-16y=7 | | 6(6g-2)+8(1+5g)=2g | | 6n-32=3n+7 | | 2x^2-4x=1.33333 | | 7t-6=330 | | (7+u)(5u-6)=0 | | 7x+8x+2x=12 | | -69=6(-3n-2)-(-5n-8) | | 19=x-32 | | A(-8)= |

Equations solver categories